Pengaruh bimbingan kelompok teknik permainan simulasi terhadap peningkatan komunikasi reseptif siswa tunarungu - Erlin Fitria; Dian Yudhawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
There are several problems faced by 14 deaf students as the subject of this research. They get diffiulties in understanding long sentences, connotative meaning, and they lack on vocabulary. Their inability in hearing makes them rely on their vision to gather information. Considering the reason of their difficulties, visual and attractive learning media are needed for deaf students. Group guidance on simulation game technique is a counseling guidance service that directs students to reflect daily activities in the form of games using physical media such as blue cards, OK cards and chance cards. In the group guidance of the simulation game technique, students learn to understand new vocabulary of the role played and can acquire vocabulary. The more vocabulary mastered will support students' ability to have receptive communication. To prove the hypothesis that the group guidance of simulation game technique influences the improvement of receptive communication of deaf students in SLB.B Wiyata Dharma 1, the Mann Whitney U Test analysis is used. Based on Mann-Whitney U-test Asymp Sig was obtained (2-tailed) 0.013 with an error level of 0.05 then 0.013 <0.05 means that Ho is rejected and Ha is accepted. It implies that the group guidance of the simulation game technique has an impact on increasing the receptive ability of deaf students. Therefore, group guidance on simulation game techniques can be used as an alternative learning media to improve receptive communication for deaf students.